An Experience Report on the Application of Fishbowl Active Method in Systems Analysis and Design Teaching - Castro, Vitor de Souza; Oliveira, Sandro Ronaldo Bezerra (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
The use of active methodologies to teach software engineering is a frequent strategy. As such, problem-based learning, flipped classroom in seminar format, and project-based learning are more widely used by teachers. Contrary to the most commonly used active methodologies, the Fishbowl presents itself as an approach with references in health and linguistics fields, but few reports in the computing area. In this context, the current research aims to present an experience report on the use of the Fishbowl in a Software Engineering course, specifically in the Systems Analysis and Design subject. Definition of the theme, definition of execution mechanics, execution of the Fishbowl session, and evaluation were the methodology activities used to develop and evaluate Fishbowl. The results of the Fishbowl session indicated positive points related to knowledge exchange between students. Furthermore, in a sentiment analysis on students’ feedback, 79% indicated the emotion of trust out of 90% positive feelings. In conclusion, the possibility of use in other subjects in the software engineering field is highlighted.